The importance of social media sites in improving the performance of the services provided.: Field study from the perspective of a sample of students from the Department of Psychology at Badji Mokhtar Annaba University - Salmi, Samir; Boumengar, Mourad (Journal of Human Sciences, 2022)
What role can social media play in the university community and how can the quality of services offered to them be improved? This is what we discussed in this article, focusing on the concepts of study variables from the perspective of consumers of these services. Through an online questionnaire based on the responses of a sample stratified of 220 students from the Department of Psychology of Baji Mukhtar University, the study achieved a series of results, the most important of which is the positive impact of social media in the delivery of services to students, as well as identifying the most significant barriers the Department faces in optimizing the use of social media sites.